ANALISIS FINANSIAL DAN STRATEGI PENGEMBANGAN USAHATANI JAMUR TIRAM PUTIH DI DESA PAMPANGAN KECAMATAN SEKINCAU KABUPATEN LAMPUNG BARAT - Mukti, Octa Primanda; Haryono, Dwi; Marlina, Lina (Jurnal Ilmu-Ilmu Agribisnis, 2017)
This study aims to analyze financial viability of oyster mushroom farming and to arrange strategies of developing oyster mushroom farming. This research is located in Sekincau District of West Lampung which is intentionally chosen with the consideration that it has good prospects in the field of horticulture, especially the oyster mushroom. Respondents include three farmers cultivating oyster mushrooms. The research was conducted in February 2016. The first objective is analyzed quantitatively by using financial analysis (Net B / C, NPV, IRR, and Payback Period) with a compounding factor (CF) of 9 percent and the second goal is analyzed descriptively with SWOT analysis. The results showed that the oyster mushroom farming in West Lampung was feasible and profitable to be pursued. Financially, the business is still viable because the NPV and Net B / C is higher than 1, and the value of IRR is higher than the interest rate.Â  Strategy priority to develop oyster mushroom farming consists of improving the quality of oyster mushroom products in order to attain physical and non physical assistance from government, widening marketing networks, and improving the use of appropriate technology in farming.Key words : development strategiy, financial analysis, and oyster mushroom